2022
DOI: 10.1182/bloodadvances.2021006574
|View full text |Cite
|
Sign up to set email alerts
|

BTK inhibitors impair humoral and cellular responses to recombinant zoster vaccine in CLL

Abstract: Vaccinations effectively prevent infections; however, patients with chronic lymphocytic leukemia (CLL) have reduced antibody responses following vaccinations. Combined humoral and cellular immune responses to novel adjuvanted vaccines are not well characterized in CLL. In an open-label, single-arm clinical trial, we measured the humoral and cellular immunogenicity of the recombinant zoster vaccine (RZV) in CLL patients who were treatment naïve (TN) or receiving Bruton tyrosine kinase inhibitor (BTKi) therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 27 publications
3
20
0
Order By: Relevance
“…Along this line, we observed a low seroconversion rate of 43% and a significant 96% decrease of antibody titer levels in B-cell lymphoma patients treated with BTKi. The negative impact of the latter on serologic response might be attributable to the BTKi-mediated block of the B-cell receptor signaling and was comparable to the findings of others [ 18 , 19 , 26 , 50 , 51 ]. The anti-CD38 therapy results indicated a depletion of antibody-producing plasma cells and was associated with a weak or non-existent response to COVID-19 vaccines in previous trials [ 21 , 48 , 52 ].…”
Section: Discussionsupporting
confidence: 89%
“…Along this line, we observed a low seroconversion rate of 43% and a significant 96% decrease of antibody titer levels in B-cell lymphoma patients treated with BTKi. The negative impact of the latter on serologic response might be attributable to the BTKi-mediated block of the B-cell receptor signaling and was comparable to the findings of others [ 18 , 19 , 26 , 50 , 51 ]. The anti-CD38 therapy results indicated a depletion of antibody-producing plasma cells and was associated with a weak or non-existent response to COVID-19 vaccines in previous trials [ 21 , 48 , 52 ].…”
Section: Discussionsupporting
confidence: 89%
“…34 BTKi therapy compared with treatment naïve patients. 38 BCL2i, like venetoclax, was found to be associated with decreased seroconversion rate, while the response rates were lower when combined with anti-CD20 antibodies. 22 In CLL patients with venetoclax monotherapy, some developed a positive response but with low Ab titers.…”
Section: Discussionmentioning
confidence: 92%
“… 27 , 37 A recent study evaluated the humoral and cellular response of the recombinant zoster vaccine in CLL patients, which indicated that both immune responses were attenuated in those on BTKi therapy compared with treatment naïve patients. 38 BCL2i, like venetoclax, was found to be associated with decreased seroconversion rate, while the response rates were lower when combined with anti‐CD20 antibodies. 22 In CLL patients with venetoclax monotherapy, some developed a positive response but with low Ab titers.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…2021 [ 26 ] CLL SARS-CoV2 vaccine 14 21% Herishanu Y, Blood 2021 [ 33 ] CLL SARS-CoV2 vaccine 50 16% 1) Age ≥ 65 years 2) Active treatment 3) Baselinge IgG levels <550 mg/dL 4) Baseline IgM levels <40 mg/dL 5) Male sex Zent C, Leukemia 2021 [ 61 ] WM + CLL rVZV vaccine 32 75% 1) Longer duration of pre-vaccination BTKi treatment Pleyer C, Blood 2021 [ 62 ] CLL HBV vaccine 26 4% Pleyer C, Blood 2021 [ 62 ] CLL rVZV revaccine 41 41% Benjamini O, Haematologica 2022 [ 21 ] CLL SARS-CoV2 vaccina 106 23% 1) Active treatment Shen Y, Br J Haematol 2022 [ 35 ] CLL SARS-CoV2 vaccine 21 15% 1) Lower baseline IgM serum levels 2) Active therapy Bacova B, Clin Exp Med. 2022 [ 28 ] B-NHL+ CLL SARS-CoV2 vaccine 16 19% Haggenburg S, Blood Adv 2022 [ 27 ] CLL SARS-CoV2 vaccine 38 27% 1) Older age 2) Low baseline IgG4 serum levels 3) Low baseline NK and B-cells counts 4) Use of rituximab, venetoclax and CD-19 directed CAR-T cells Diamantopoulos P, Ther Adv Hematol 2022[ 54 ] CLL SARS-CoV2 vaccine 7 14% Pleyer, Blood Adv 2022 [ 63 ] CLL rVZV vaccine 50 40...…”
Section: Ibrutinib and Other Btk Inhibitorsmentioning
confidence: 99%